AB1065 THE UTILISATION OF S100 PROTEINS TESTING IN PEDIATRIC RHEUMATOLOGY PATIENTS IN A TERTIARY CARE INSTITUTION AND IMPLICATIONS FOR CARE. (June 2019) - Tronconi, Elena; Aljaberi, Najla; Merritt, Angela; Grom, Alexei; Schulert, Grant; Huggins, Jennifer; Henrickson, Michael; Brunner, Hermine
Abstract : Background: S100 proteins are calcium-binding proteins of increasing value as biomarkers in various inflammatory conditions. The two highly studied members in this family, S100A8/9 and S100A12 have been considered sensitive biomarkers of disease activity in rheumatologic disorders as rheumatoid arthritis (1) and juvenile idiopathic arthritis (JIA) (2). They are considered more accurate than conventional inflammatory indices such as the erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) (3). Objectives: To evaluate the utilization of S100 proteins in the clinical setting as supportive diagnostic tools as well as their performance in evaluating disease activity. Methods: Patients seen at the hospital's specialty clinics who had S100 proteins tested during their care from April 2017 to August 2018. A retrospective chart review was performed to collect data on serum S100 protein levels, other inflammatory markers as CRP and disease activity measured as active joint count (AJC) in JIA patients and the presence of systemic symptoms in systemic JIA (sJIA) patients. Graphpad Prism Version 7.05 was used for data analyses. Descriptive statistics were calculated for all variables. Comparisons were done by the Mann-Whitney U test and the Kruskal-Wallis test. Spearman correlation were calculated to assess association between S100 proteins and other numerical variables. Results: A total of 164 patients were included. All 164 patients had S100A8/9 collected but only 151 had S100A12 samples. Patients with sJIA had higher levels of S100A8/9 and S100A12 compared to patients with non-systemic JIA (nsJIA) and periodic fever syndrome (PFS). CRP levels were not statistically different among diagnosis while S100 proteins were. Both S100A8/9 and S100A12 showed a good ability to differentiate sJIA from PFS (AUC=0.76 for both) compared to AUC=0.6 for CRP. At a cut-off value of 164 ng/ml, S100A12 was 71% sensitive and 73% specific in differentiating between sJIA and PFS (Figure 1 ). In JIA there was no correlation between S100 protein levels and AJC, either sJIA or nsJIA patients. S100A8/9 and S100A12 were significantly elevated in active sJIA patients compared to inactive ones while CRP levels were not different. S100 proteins levels where significantly higher during a flare of PFS compared to inactive disease, as well as CRP. There was no difference in S100 proteins and CRP in patients with or without tocilizumab treatment (small number on tocilizumab). Conclusion: S100A8/9 and S100A12 are particularly elevated in sJIA compared to nsJIA and PFS. They are useful in distinguishing sJIA from other diagnoses with similar presentations, such as PFS. S100 proteins were significantly higher in active disease status of patients with sJIA and PFS compared to inactive status and their levels were closer associated with sJIA disease activity than CRP. The S100 proteins could provide valuable data in the work-up of patients with autoinflammatory conditions and monitoring disease activity in sJIA and PFS patients. References: [1] Choi IY, Gerlag DM, Herenius MJ, Thurlings RM, Wijbrandts CA, Foell D, et al. MRP8/14 serum levels as a strong predictor of response to biological treatments in patients with rheumatoid arthritis. Annals of the Rheumatic Diseases. 2015;74:499-505. [2] Foell D, Wittkowski H, Hammerschmidt I, Wulffraat N, Schmeling H, Frosch M, et al. Monitoring Neutrophil Activation in Juvenile Rheumatoid Arthritis by S100A12 Serum Concentrations. Arthritis and Rheumatism. 2004. [3] Frosch M, Ahlmann M, Vogl T, Wittkowski H, Wulffraat N, Foell D, et al. The myeloid-related proteins 8 and 14 complex, a novel ligand of toll-like receptor 4, and interleukin-1β form a positive feedback mechanism in systemic-onset juvenile idiopathic arthritis. Arthritis and Rheumatism. 2009. Disclosure of Interests: Elena Tronconi: None declared, NAJLA ALJABERI: None declared, Angela Merritt: None declared, Alexei Grom Grant/research support from: Novartis, AB2Bio, Novimmune, Consultant for: Novartis, Grant Schulert: None declared, Jennifer Huggins: None declared, Michael Henrickson: None declared, Hermine Brunner Grant/research support from: Bristol-Myers Squibb, Pfizer, Consultant for: Pfizer, Bristol-Myers Squibb, Janssen, Novartis, Lilly, Roche, GlaxoSmithKline, Sanofi, Speakers bureau: Novartis, Roche